KEHIDUPAN SOSIAL EKONOMI PETANI DI DESA MALIKU SATU KECAMATAN AMURANG TIMUR KABUPATEN MINAHASA SELATAN - Pangi, Joris; Lasut, Jouke J.; Paat, Cornelius J. (Universitas Sam Ratulangi, 2020)
The characteristics of Indonesia as an agrarian country that mostly earn a living in agriculture. The majority of the population lives in rural areas and depends on the primary sector, especially agriculture. Agriculture is one source of income and economy for humans, by having fertile soil and plants can make a person meet their daily needs. Therefore, the results issued from the agricultural land are required to have a certain amount of assets, namely the amount of agricultural assets.In Maliku Satu village, it is seen from the potential of natural resources that are still abundant so that this village is also a mainstay of productivity in agriculture, by relying on commodity crops, horticulture and annual crops such as copra and rice. At first glance, if you see some of the results of these commodities will actually promise the future for the farming community in the village of Maliku Satu. However, when seen from the improvement of the lives of the Coconut Farmers in Maliku Satu Village, they have not yet fully enjoyed the potential reliable results. Even though the coconut plantations of the Maliku Satu village community are very promising.Keywords: Farmers, Socio-Economic Life